2015
DOI: 10.1556/1886.2015.00029
|View full text |Cite
|
Sign up to set email alerts
|

ABO/Rh Blood Groups and Risk of HIV Infection and Hepatitis B among Blood Donors of Abidjan, Côte D’Ivoire

Abstract: Hepatitis B and HIV infection are two viral infections that represent real global public health problems. In order to improve their management, some hypotheses suggest that genetic predispositions like ABO and Rh blood groups would influence the occurrence of these diseases.The aim of the present study was to examine the association between ABO and Rhesus blood groups and the susceptibility to HIV infection and hepatitis B.We conducted a cross-sectional and analytical study in a population of voluntary blood d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
47
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 9 publications
4
47
1
Order By: Relevance
“…12 There are many similar studies with the study of Mohammadali et al, that cannot find a significant correlation between HBV infection and blood groups. [13][14][15][16][17] In these studies, usually HBV infection was more commonly detected in patients in blood group O. 13,14,16 Only in the study of Siransy et al, HBV infection were more frequently observed in blood group A and in blood group B in the study of Behal et al 15,17 In these five studies, the results of Rh blood group were different ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 There are many similar studies with the study of Mohammadali et al, that cannot find a significant correlation between HBV infection and blood groups. [13][14][15][16][17] In these studies, usually HBV infection was more commonly detected in patients in blood group O. 13,14,16 Only in the study of Siransy et al, HBV infection were more frequently observed in blood group A and in blood group B in the study of Behal et al 15,17 In these five studies, the results of Rh blood group were different ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17] In these studies, usually HBV infection was more commonly detected in patients in blood group O. 13,14,16 Only in the study of Siransy et al, HBV infection were more frequently observed in blood group A and in blood group B in the study of Behal et al 15,17 In these five studies, the results of Rh blood group were different ( Table 2). Many studies are also available that do not have statistical data about the relationship between ABO/Rh blood groups and HBV infection ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…"ABO" and "Rhesus" blood group antigens are major human blood group system antigens with prime importance in transfusion medicine. [1] The blood type of an individual defined by small carbohydrate epitopes depends on the presence or absence of genes "A" and "B". The gene is positioned on chromosome 9q34 and consists of 7 exons spread over 18kb called "ABO" blood groups.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, HBsAg seroprevalance was the highest in patients with O blood group among a cohort of 330 blood donors, however, the association was not statistically significant (22). Siransy et al (23) have found that O blood group of individuals were infected with HIV and HBV infection more frequently than those with non-O blood group. In a comprehensive study including antenatal screening tests, B and AB blood groups were observed to be associated with increasing HBV infection (24).…”
Section: Discussionmentioning
confidence: 99%